Double workouts: What's your nutrition game plan? - Clark, N. (1999)
Many athletes are faced with the nutrition challenges presented by double workouts, back-to-back events and tournaments that require top performance hours on end, sometimes days in a row. The athletes who pay careful attention to what they eat are able to conquer these events and win with good nutrition. But, as one athlete commented, "Most skaters don't even think about what they'll be eating between races. They just eat whatever's around -- a box of donuts, a bag of chips, or nothing." These athletes, and others who give no thought to their sports diet, cheat themselves of the ability to refuel and play hard again. Here are some tips for success with repeated bouts of exercise.